Developing a coordinated regulation schedule to prevent damage to the environment by vehicles and improve the structure of the energy system: evidence from the city of Baku (Azerbaijan) - Baghirov, Mirhamid; Багіров, Мірхамід (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The scale of road traffic is constantly increasing all over the world, which is the basis and indispensable condition for sustainable economic growth, on the one hand, and the source of a complex of transport and environmental problems, on the other. One of the most pressing problems is the congestion of road networks. Goal. The purpose of the article is the analysis of the way to organize the creation of an effective system that controls traffic in an urban agglomeration. Methodology. This article analyzed the case of one of the main avenues of Baku to develop a coordinated regulation schedule for reducing vehicles dam age to the environment by waiting at a red light, as well as for improving the structure of the energy system in the developing countries, especially in Ukraine, which has been suffering from war. Results. For this reason, in the article a proposal was made to improve the efficiency of traffic management at the main inter section of Matbuat avenue in Baku, the number of vehicles moving on the avenue was studied and the traffic light timings report was made at all intersections, the reports were adapted to the main roadway, and a green wave graph was constructed. Originality. The methodology for estimating environmental and economic damage from the impact of motor vehicles on the urban ecosystem, including indexation coefficient has been improved. The methodical bases of the design of a complex of environmental measures to reduce the impact of vehicles on the environment of Baku have been substantiated. The article provides a basis for the design of a complex of environmental measures. Practical value. A set of measures has been developed to reduce pollution from city vehicles, which can be used in regional and municipal programs.
Розробка узгодженого графіка регулювання для запобігання шкоди транспортним засобам навколишньому середовищу та покращення структури енергетичної системи: Докази з міста Баку (Азербайджан)
Keywords: Baku city; intersection; "Green Wave"; "off-peak" hours; coordinated regulation system; місто Баку; перехрестя; «Зелена хвиля»; «непікові» години; узгоджена система регулювання; 656.13; 10.30977/AT.2219-8342.2023.52.0.07